Recovering from COVID-19 - A Process Characterised by Uncertainty: A Qualitative study - Marie Engwall; Karin Törnbom; Hanna C. Persson; Annie Palstam (Medical Journals Sweden, 2022)
Objective: To obtain a deeper understanding of the lived experiences of patients with COVID-19, the recovery process and consequences for everyday life 6 months after hospital discharge. Design: An explorative qualitative study using individual interviews. Subjects: A purposive sampling was applied to recruit persons who had received inpatient hospital care, were discharged approximately 6 months previously, were of working age and had persistent self-reported symptoms at a 3-month follow-up appointment. Methods: Semi-structured interviews were conducted with 15 participants (10 men, 5 women), which were then transcribed and analysed with inductive thematic analysis. Results: Three themes were identified: "Status of recovery - two steps forward, one step back", "Remaining symptoms caused limitations in everyday life" and "Strategies for recovery". Participants indicated the recovery process through 6 months after discharge was a challenging road, often involving setbacks. A wide range of persistent, fluctuating, or new symptoms negatively impacted many areas of daily life, with fatigue and lack of energy being especially prominent. Participants used a variety of strategies to cope and recover. Conclusion: This study increases our knowledge of the lived experiences of COVID-19 based individual experiences. Unexpected symptoms in the recovery process were described and not always possible to forecast. LAY ABSTRACT The aim of this study was to gain a deeper understanding of the lived experiences of patients with COVID-19, the recovery process and impacts on everyday life 6 months after hospital discharge. Included participants were discharged 6 months previously from inpatient care, and selected from a patient cohort. All participants had selfreported symptoms at a 3-month follow-up and were of working age. Individual interviews were conducted with 15 participants (10 men, 5 women) following an interview guide developed together with patient partners, who were contributing to the research process. The interviews were analysed using thematic analysis. The results of the analysis revealed that the recovery process was experienced as a rocky and uncertain road, often involving setbacks. A wide range of persistent, fluctuating or newly developed symptoms had negative impacts on many areas of daily life, with fatigue and lack of energy being especially challenging. Participants used a variety of strategies to manage everyday life and recover.